Enhanced luminescence properties of Ca1+xSr2−xAl2O6:Eu3+ (0 ≤ x ≤ 1) red phosphors based on composition modulation. Issue 21 (6th April 2021) - Shen, Biao; Xu, Jianghang; Mao, Qinan; Zhong, Jiasong
Abstract : A series of Ca1+ x Sr2− x Al2 O6 :Eu 3+ (0 ≤ x ≤ 1) red-emitting phosphors with adjustable optical properties and excellent quantum efficiency was developed for potential applications in warm WLEDs. Abstract : A series of solid solution Ca1+ x Sr2− x Al2 O6 :Eu 3+ (0 ≤ x ≤ 1) phosphors has been successfully synthesized via a high-temperature solid-state method. The phase structures, photoluminescence performances, and fluorescence lifetimes, as well as the thermal stability properties, have been systematically investigated. All of the samples possess a cubic structure system and belong to the Pa 3̄(205) space-group. Owing to the 5 D0 → 7 F2 transition of the Eu 3+ ions, the photoluminescence emission (PL) spectra demonstrate a strong red emission band at around 612 nm. As the Sr 2+ ions have been substituted by Ca 2+ ions in the CaSr2 Al2 O6 :Eu 3+ composition, the luminous intensities are gradually enhanced owing to the average bond lengths of Ca–O, Sr/Ca–O, and Sr–O, which are shorter. In addition, the PL intensities at 423 K for the CaSr2 Al2 O6 :0.02Eu 3+, Ca1.5 Sr1.5 Al2 O6 :0.02Eu 3+, and Ca2 SrAl2 O6 :0.02Eu 3+ phosphors retain 84.5%, 76.1%, and 75.7% of their intensities, respectively, compared with their initial intensities at 303 K. The results demonstrate that high-performance Eu 3+ -activated red-emitting phosphors can be obtained via cation substitution.